The relationship between cognitive emotion regulation strategies and emotional manipulation among health colleges students: a cross-sectional correlational study - Alwesmi, Mai B.; Bayounes, Rasha Mohammed; Binrushaydan, Norah Nasser; Alanazi, Maha Ahmad; Salem, Raghad Mohamed; Alomairi, Raghad Ahmad; Albugami, Amal Zaid; Alzahrani, Ebtisam Mohammed; Alahmari, Lama A.; Youssef, Naglaa (Frontiers in Psychiatry, 2024)
Emotional intelligence is commonly associated with career success. Employees with higher emotional intelligence tend to reap greater benefits. However, emotional manipulation has been reported as a dark side of emotional intelligence, which refers to the self-perceived ability to control the emotions and actions of others for self-benefit. Healthcare professionals with high emotional intelligence often improve the overall patient experience. However, their ability to manipulate emotions can have a detrimental impact on the quality of treatment. This cross-sectional correlational study assessed cognitive emotion regulation strategies (CER) and emotional manipulation among students of health colleges. Two instruments were used to collect the data: 1) the emotional manipulation scale and 2) the cognitive emotion regulation questionnaire. A total of 362 students from health colleges responded to the questionnaire. The students had a moderate tendency to use emotional manipulation (25.09 ± 6.79 out of 50). The most frequently used CER strategies included adaptive strategies such as positive reappraisal with a mean score of 7.45 ± 2.15 out of 10 and maladaptive strategies such as rumination with a mean score of 7.33 ± 2.23 out of 10. The emotional manipulation score had a small but statistically significant negative correlation with two adaptive CER strategies: positive refocusing (r = -0.146, p = 0.005) and focus on planning (r = -0.144, p = 0.006). This study sheds light on the relationship between CER strategies and emotional manipulation, suggesting that poor use of adaptive strategies is associated with emotional manipulation. This finding highlights the importance of designing interventional programs that improve the ability of health colleges students to regulate their cognitive and emotional responses, thus improving their overall well-being and performance as future healthcare workers.